Evolving Crisis Management - Current Jobs and Required Employee's Skills and Characteristics Analysis - Davor Labaš; Andrijana Pršir; Julija Puškar (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
With digitalization transforming the industries, as well as crisis management field, most managers are asking the following questions. What do organizations consider under today's crisis management? Which knowledge, technological capabilities, education and competences do organizations require from their employees in the crisis management field? Considering that fairly large #of organizations do not have adequate crisis management systems in place, and accordingly organizations are not sufficiently prepared for crisis situations, it is necessary to further develop crisis preparedness and response capacities, whereas clear understanding of new methods and crisis management activities can contribute to adequate response to organizational crises. This paper will determine what constitutes the modern crisis management, new job market demands, and further streams of research. Accordingly, the aim of this paper is to identify modern crisis management jobs, organizational needs for jobs, employee's assignments, scope of activities, along with instruments and methods. Analysis was accomplished through qualitative content research of online job ads (vacancies) on online platform LinkedIn, and it identified a mix of skills and characteristics needed for jobs in the crisis management field. In addition, this paper provides an overview and mapping of the contemporary crisis management field (which concepts can be classified under the crisis management field, identifies similarities and differences among the concepts), provides guidelines and basis for further theoretical and empirical research and development of the crisis management field. The contribution of this paper is in identification of guidelines for further research, especially from the aspect of current organizational needs and identifying demand for crisis management employees. The findings can help managers and human resource teams further develop the knowledge on crisis management and crisis management expert's requirements.
Keywords: 650; Crisis management; Job content analysis; LinkedIn; Job requirements; Organizations